An Evaluation of SPARC Protein as a Serum Biomarker of Chronic Rhinosinusitis. (2nd October 2018) - Asmar, Marc‐Henri; Gaudreau, Annie; Maniakas, Anastasios; Mfuna Endam, Leandra; Desrosiers, Martin
Abstract : Objective: Precision medicine initiatives for chronic rhinosinusitis (CRS) management suggest tailoring treatment to the patient's individual disease profile; however, serum biomarkers for evaluation of disease activity or predicting response to therapy are lacking in CRS. Epithelial‐to‐mesenchymal transition (EMT) has been described as a component of barrier dysfunction in CRS. SPARC (secreted protein acidic and rich in cysteine) is a marker of EMT that has previously been identified in sinus epithelium by gene expression profiling. We wished to determine if SPARC could represent a serum biomarker for CRS by verifying (1) if SPARC could be detected in serum, (2) whether levels were sensitive to disease burden reduction following surgery, and (3) if it could predict response to therapy. Study Design: Prospective. Setting: Tertiary care center. Subjects: Patients with CRS undergoing endoscopic sinus surgery (ESS). Methods: Twenty‐six patients undergoing ESS for CRS were prospectively recruited. Serum was collected at the time of surgery and 4 months following ESS and SPARC level measured using enzyme‐linked immunosorbent assay. Postoperative outcome was characterized as "remission" or "unfavorable" based on symptomatology and endoscopy. Results: SPARC could be detected and measured in serum in all subjects. Following ESS, SPARC levels decreased by 33% ( P =. 005) but did not predict evolution at 4 months postsurgery ( P =. 94). Conclusion: SPARC may be an interesting serum biomarker of disease activity in CRS, as it can be reliably measured and decreases following successful reduction of disease burden after surgery. However, it does not predict post‐ESS evolution, suggesting that the link between EMT and outcome is not linear.